Our grateful dead : stories of those left behind - Despret, Vinciane; Muecke, Stephen, 1951- (Minneapolis : University of Minnesota Press, 2021)
"Vinciane Despret's unique storytelling, woven with ethnography and family history, assembles accounts of those living their daily lives with their dead"--
Taking care of the dead -- Allowing yourself to be instructed -- The ties that keep the living and the dead together -- Watching over the things that matter -- Extending the work : the generosity of the dead -- Uncertain thoughts -- Putting our trust in spirits : how to call on them -- Protecting voices.
Translated from the original French into English.
"Originally published in French as Au bonheur des morts, Récits de ceux qui restent. Copyright Éditions La Découverte, Paris, 2015, 2017."
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on December 07, 2021).
JSTOR
Keywords: Dead; Mourning customs; Grief; Death -- Social aspects; Death -- Psychological aspects; Morts; Deuil -- Coutumes; Chagrin; Mort -- Aspect social; Mort -- Aspect psychologique; grief; SOCIAL SCIENCE / Death & Dying; Dead; Death -- Psychological aspects; Death -- Social aspects; Grief; Mourning customs